2010
DOI: 10.3233/jad-2010-090631
|View full text |Cite
|
Sign up to set email alerts
|

Brain SPECT Findings of Anosognosia in Alzheimer's Disease

Abstract: Anosognosia is a common symptom of dementia. The aim of this study was to evaluate the contribution of different regions of the brain to anosognosia in Alzheimer's disease (AD) brains using single photon emission computed tomography (SPECT). Forty-two patients with AD were included in this study. After clinical interviews with the patients and their relatives, the patients were divided into two groups: Anosognosia and No-anosognosia. The patients were studied regarding the severity of dementia. They underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 0 publications
1
30
1
1
Order By: Relevance
“…This finding is consistent with one previous imaging study (48). However, these medial prefrontal relationships are not entirely consistent with other studies that have observed an association between poor awareness in AD and right hemisphere dysfunction, particularly involving frontal and temporal regions (16, 17, 4952). There is no “gold standard” for assessment of insight in AD and instruments may include clinician ratings, questionnaire-based methods, performance-based methods, phenomenological methods, or a combination of methods (53).…”
Section: Discussioncontrasting
confidence: 56%
“…This finding is consistent with one previous imaging study (48). However, these medial prefrontal relationships are not entirely consistent with other studies that have observed an association between poor awareness in AD and right hemisphere dysfunction, particularly involving frontal and temporal regions (16, 17, 4952). There is no “gold standard” for assessment of insight in AD and instruments may include clinician ratings, questionnaire-based methods, performance-based methods, phenomenological methods, or a combination of methods (53).…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, a substantial body of evidence suggests that the vascular factor may play an essential role in plotting the pathogenetic background of AD [11,12], Although cerebrovascular amyloidosis, is a common finding in Alzheimer's brains [13], the structural deformities of the brain capillaries, may be a crucial factor, resulting in hypometabolism of brain areas related with mental activities [14]. Studies based on positron emission tomography have revealed regional metabolic decrease in patients suffered from MCI or possible AD [15,16], which correlates with the dementia's rate [16]. It is rational, that vascular risk factors may increase the prevalence of AD [17].…”
Section: Introductionmentioning
confidence: 99%
“…Medial prefrontal cortex (PFC) in the right frontal lobe appears to play a crucial role in self-appraisal. 12-15 This area is important for social cognitive processing, and, in particular, knowledge about the self, 16 and this may confound assessments of the neuroanatomy of self-appraisal focusing on social content. Moreover, the precise area within medial PFC that is critical for self-appraisal remains to be specified.…”
Section: Introductionmentioning
confidence: 99%